Discussing the design through drawing: transitional desire and procedural trajectories - Magalhães, Graça Maria Alves dos Santos (2014)
Design represents the commitment of the artificial with nature – the artifact as symbolic cultural representation. Herein, drawing is the skill activity of the designer as renewed desire it transforming the world. Therefore, drawing is the material of design as medium of the representation, such as technical and interpretive expression of the author's imagination from an external program (brief). Hence, we propose drawing as a path performed by author’s desire that symbolically reveals the subject of design in a specific level. The artifact as primordial income for the conceptual design process comes out of the drawing tools as practice that elevates the cultural representation. The pattern of drawing can be, symmetrical or asymmetrical, the link that joins two levels of the artifact, instrumental and critical, it becoming the basis for design’s narrative. In this case, drawing skills convey and supporting the cultural expression showing design as a particular and symbolic cultural artifact. As context we refer the analysis of representative designers in the Portuguese geographic and cultural environment. We hypothesized that cultural and symbolic features result according to the artifact’s identity. We seek the goal of the analysis according to the significance of drawing in the discipline of design. This research intends to scientifically integrate the ontological analysis of drawing in relation to design through the presented Portuguese examples.